Using the Synthetic Control Method to Evaluate the Impact of a Land-Based Gambling Ban on Crime - Žofčák, Jakub; Šíma, Josef (Journal of gambling studies, 2024)
We use the synthetic control method to examine whether land-based gambling ban has an effect on crime in a given city. In a sample of four Czech cities where the ban was introduced, we show that these cities had roughly the same crime rate development in the years after the ban as the control cities without the ban, showing that there is no significant impact. As this is, to our knowledge, the first use of the synthetic control method in the context of gambling, the main contribution of this study lies in demonstrating the possibilities in its use. Employing this versatile method may improve the current situation where many gambling impact studies suffer from the absence of a control group or an identification strategy to confirm causal relationship. Last but not least, the results of this study make an important contribution to the debate on blanket measures in gambling regulation; although pathological gambling is linked to crime, banning this activity may not lead to the expected consequences.
Keywords: Panel data; zločin; Synthetic control method; Gambling; návykové chování; Crime; Criminality; Humans; Česká republika; hráčství; lidé; Behavior, Addictive; Czech Republic